2016
DOI: 10.1590/s0102-05362016003012
|View full text |Cite
|
Sign up to set email alerts
|

Potential of rosemary leaves and branches to enhance storage life of onion bulbs

Abstract: Although its importance as vegetable, a considerable amount of onion bulbs is lost in storage. That's why storage condition is one of the most important issues to maintain post-harvest quality. For this purpose, a factorial experiment based on randomized complete block design with two factors and three replicates was carried out. The factors were storage conditions of onion bulbs with five levels (4oC in the seed storage apparatus, 25 and 30oC without using rosemary leaves and branches in the incubator, and 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As in Peng et al (2016), there was no statistical variation for fresh weight loss between the control and the concentrations of 0.2 and 1% allicin. Bina et al (2016) observed a lower weight reduction in onions stored at 25 °C and 30 °C with rosemary branches and leaves when compared to storage for the same period and temperature conditions, without the rosemary branches and leaves. The application of garlic extract decreased the antioxidant activity and total phenolics ( Figure 1A) whereas for the pepper extract it was observed an increase in the antioxidant activity and total phenolics at concentrations of 5, 15, 20 and 25% ( Figure 1B), this behavior was similar to Cao et al (2009) with an increase of total phenolics during storage of Eriobotrya japonica when tested methyl jasmonate, an elicitor of plant defense.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…As in Peng et al (2016), there was no statistical variation for fresh weight loss between the control and the concentrations of 0.2 and 1% allicin. Bina et al (2016) observed a lower weight reduction in onions stored at 25 °C and 30 °C with rosemary branches and leaves when compared to storage for the same period and temperature conditions, without the rosemary branches and leaves. The application of garlic extract decreased the antioxidant activity and total phenolics ( Figure 1A) whereas for the pepper extract it was observed an increase in the antioxidant activity and total phenolics at concentrations of 5, 15, 20 and 25% ( Figure 1B), this behavior was similar to Cao et al (2009) with an increase of total phenolics during storage of Eriobotrya japonica when tested methyl jasmonate, an elicitor of plant defense.…”
Section: Resultsmentioning
confidence: 76%
“…In order to improve the defense and resistance of plants, studies involving the use of plant extracts have increased in recent years. The use of extracts of rosemary (Rosmarinus officinalis), garlic (Allium sativum), pepper http://cpsjournal.org (Capsicum baccatum) and lemongrass (Cymbopogon citratus) have been tested for their ability to protect other cultures (Cruz et al 2013, Poonpaiboonpipat et al 2013, Peng et al 2015, Bina et al 2016.…”
Section: Highlighted Conclusionmentioning
confidence: 99%
“…In a study on the essential oils of ten plants, 21 recommended that the essential oils could be a potential source of eco-friendly botanical fungicide, after long term and wide ranging trials to exhibit absolute fungi toxic activity up to 100% growth inhibition. Bina et al 24 reported that the application of rosemary fresh leaves and branches can improved the storage life of onions considering its simplicity and efficacy in decreasing the storage cost, the weight loss and sprouting without causing any environmental toxicity. Therefore, applying rosemary leaves and branches to reduce germination and potato weight, the fungal infection and decay is the most effective approach as compared to the recommended chemical sorirradiation storage in potato bulbs.…”
Section: Discussionmentioning
confidence: 99%